Депривация глутатионовой системы в цитозоле и митохондриях головного мозга крыс с хронической алкогольной интоксикацией: защитные эффекты тиольных антиоксидантов - Беленичев, И. Ф.; Кучер, Т. В.; Бєленічев, Ігор Федорович; Кучер, Тетяна Володимирівна; Belenichev, I. F.; Kucher, T. V. (My University, 2016)
У статті висвітлено проблему пошуку нових методів корекції депривації глутатіонової системи головного мозку при хронічній алкогольній інтоксикації (ХАІ) шляхом застосування тіольних антиоксидантів гептралу, N-ацетилцистеїну і тіоцетаму. Однією із ланок пошкодження нейронів при ХАІ є дефіцит відновлених тіольних сполук. Експериментальне моделювання ХАІ призводило до депривації глутатіонової системи і ініціюванню нітрозуючого стресу у мозку експериментальних тварин. Курсове введення досліджуваних тіольних антиоксидантів тваринам з ХАІ призводило до нормалізації системи глутатіону і гальмуванню нітрозуючого стресу в головному мозку. Найбільшу активність продемонстрував тіоцетам, який перевершував дію не тілько референс-препарату пірацетама, але й гептрала і N-ацетілцистеїна. Експериментальні дані є обґрунтуванням для застосування тіольних антиоксидантів в якості нейропротекторів в комплексній терапії при хронічній алкогольній інтоксикації. The article focuses on the problem of search of new methods of correction of the brain glutathione system deprivation and the associated with it initiation of the nitrozitive stress in chronic alcohol intoxication through the use of thiol antioxidants. Thiol antioxidants can be considered as effective NO scavengers and as positive modulators of the thiol-disulfide system. This conception is based on the fact that the main mechanisms of neuron injury in chronic ethanol consumption is the deficit of recovered thiol compounds. The violations in nitroxidergic system led to the decrease in the bioavailability of NO and to the initiation of nitrozitive stress. Thiol antioxidants - heptral, N-acetylcysteine, and thiocetam were studied as test products and pyracetam was chosen as a reference product. The aim of research was to study the influence of heptral, N-acetylcysteine and thiocetam on the indices of the glutathion system and of nitrozitive stress in the brain of rats exposed to chronic ethanol intoxication. The research was provided on 60 outbred male rats with body mass 180-220 g in the age of 4-5 months. Chronic alcohol intoxication was caused by daily administration of ethanol into the stomach.
Депривація глутатіонової системи в цитозолі та мітохондріях головного мозку щурів з хронічною алкогольною інтоксикацією: захисні ефекти тіольних антиоксидантів
The deprivation of glutathione system in the cytosol and mitochondria of rat brain with chronic alcohol intoxication: protective effects of thiol antioxidants
Keywords: хронічна алкогольна інтоксикація; система глутатіону; нітрозуючий стрес; N-ацетілцистеїн; гептрал; тіоцетам; chronic ethanol intoxication; glutathione system; nitrozitive stress; N-acetylcysteine; heptral; thiocetam